The Analysis of Employee Job Satisfaction at CV ABCD - Fani Erisha Dewi, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research uses a qualitative method, namely by analyzing and describing the problems found. This research is based on primary data and secondary data. Primary data in this study were obtained through observation, interviews, and documentation, while secondary data were obtained through books, previous research, and articles related to the research. The sample of this research is CV ABCD employees, researchers also collected data through a survey method sent to 15 employees. Job satisfaction is an emotional state that comes from knowledge and evaluation of one's job. Job satisfaction is also the result of employee responses regarding what is considered important about how good their job is. Employee job satisfaction can play an important role in creating a positive work environment, employees who are satisfied with their jobs tend to be responsible in carrying out their duties. From the results of the study, it shows that although quite a lot of employees can feel satisfaction, there are still some employees who have not felt job satisfaction either from the work environment, salary or compensation, etc. Therefore, most employees express that they do not have a clear opinion (neutral) regarding job satisfaction at CV ABCD. Therefore, most employees expressed that they did not have a clear opinion (neutral) regarding job satisfaction at CV ABCD. This research provides insights for companies to help them identify measures that can be implemented to increase employee job satisfaction at CV ABCD. With an increase in job satisfaction, it will have an impact on the overall performance of the company as expected.